2014
DOI: 10.3171/2013.8.jns13575
|View full text |Cite
|
Sign up to set email alerts
|

The callosal angle measured on MRI as a predictor of outcome in idiopathic normal-pressure hydrocephalus

Abstract: Object Different neuroimaging biomarkers have been studied to find a tool for prediction of response to CSF shunting in idiopathic normal-pressure hydrocephalus (iNPH). The callosal angle (CA) has been described as useful in discriminating iNPH from ventricular dilation secondary to atrophy. However, the usefulness of the CA as a prognostic tool for the selection of shunt candidates among patients with iNPH is unclear. The aim of this study was to compare the CA in shunt responders with that in nonresponders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 31 publications
6
92
1
9
Order By: Relevance
“…For example, our results concerning the width of the temporal horns and disproportion of SA spaces are not completely in line with those of a recent study by Virhammar et al, reporting them to be predictive markers of shunt response [35]. Although we found no significant associations with shunt response, CA was the smallest in the shuntresponsive group, and this tendency is in line with Virhammar et al The predictability of shunt response by radiological markers in previous studies [34,35] could be attributed to utilization of more sensitive measurements of shunt response (e.g., measured gait speed and detailed cognitive evaluation) than the simple clinical evaluation used here. In addition, the negative results could be due to the small number of nonresponders indicating a successful selection of patients for shunt surgery.…”
Section: Shunt Response and Radiological Markerssupporting
confidence: 93%
See 1 more Smart Citation
“…For example, our results concerning the width of the temporal horns and disproportion of SA spaces are not completely in line with those of a recent study by Virhammar et al, reporting them to be predictive markers of shunt response [35]. Although we found no significant associations with shunt response, CA was the smallest in the shuntresponsive group, and this tendency is in line with Virhammar et al The predictability of shunt response by radiological markers in previous studies [34,35] could be attributed to utilization of more sensitive measurements of shunt response (e.g., measured gait speed and detailed cognitive evaluation) than the simple clinical evaluation used here. In addition, the negative results could be due to the small number of nonresponders indicating a successful selection of patients for shunt surgery.…”
Section: Shunt Response and Radiological Markerssupporting
confidence: 93%
“…The CA is smaller in iNPH (less than 90°) than in patients with AD or normal controls [18]. Additionally, it has been reported that the CA is smaller in shunt-responsive iNPH patients than in non-responsive patients [34].…”
Section: Introductionmentioning
confidence: 97%
“…5 The results in this and a previous study of a smaller callosal angle in patients who responded to shunt surgery further support its prognostic value. 3 The significant OR Ͻ 1 for the callosal angle can be interpreted as showing that patients with a larger angle are less likely to benefit from shunt surgery.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The brain morphology in iNPH is characterized by large ventricles, enlarged Sylvian fissures, tight convexity sulci, and a small callosal angle. [4][5][6] The symptoms can be relieved by removal of CSF in patients with iNPH, either permanently by shunt implantation or temporarily by a lumbar puncture as a prognostic test (CSF tap test). 7 Radiologic evaluation of the size of the ventricles and sulci is also important in patients with other types of hydrocephalus (eg, secondary to a subarachnoid hemorrhage).…”
mentioning
confidence: 99%